LA–ICP–MS and EPMA studies on the Fe–S–As minerals from the Jinlongshan gold deposit, Qinling Orogen, China: implications for ore‐forming processes. (15th August 2014) - Zhang, Jing; Li, Lei; Gilbert, Sarah; Liu, Jia‐Jun; Shi, Wen‐Sheng; Chen, Y.J.; Santosh, M.; Chen, H.Y.; Somerville, Ian
<x xml:space="preserve">Abstract</x> The Jinlongshan gold deposit, Shaanxi Province, is a large Carlin‐type deposit in the Western Qinling Gold Province (WQGP) in the Qinling Orogenic Belt, Central China. In this study, we present new EPMA and LA–ICP–MS geochemical data on the Fe–S–As minerals at Jinlongshan, which consist mainly of pyrite, arsenian pyrite and arsenopyrite. Diagenetic pyrite (Py0) is preferentially hosted in the sedimentary rocks as rounded or framboidal aggregates. Three types of hydrothermal pyrite (Py1, Py2 and Py3) and two types of arsenopyrite (Apy1 and Apy2) were newly identified in the ores and wall‐rocks: fine‐grained Py1 and Apy1 were formed at the early mineralization stage; coarse‐grained Py2 and Apy2 were formed at the middle mineralization stage; and Py3 with stibnite were formed at the late mineralization stage. Their trace elements differ in concentrations, associations and rim–core zonations, implying different genesis and crystallization processes. Py0 is As‐poor (Au < 0.105 wt% and As < 0.094 wt%); Py1 and Py2 are Au–As‐rich (Au = 1.9–113 ppm and As up to 7.270 wt%); Py3 is Au–As‐poor (Au = 0.03–11.4 ppm and As < 0.56 wt%); and Apy1 and Apy2 show the highest Au concentration (up to 576 ppm). Co, Ni and As (±Se and Te) occur in pyrite as isomorphism, and Ag, Cu, Pb and Zn are distributed primarily as invisible or visible sulphide inclusions. The dominant state of Au in the hydrothermal Fe–S–As minerals at Jinlongshan is lattice bound Au+1, and possibly invisible Au0 nanoparticles, whereas in the diagenetic Py0, the dominant state is mainly Au0. By integrating the evidence from ore deposit geology, mineral morphology, internal structure and trace element geochemistry of the Au‐bearing Fe–S–As minerals, it is concluded that the formation of the Jinlongshan Au deposit may have been related to the regional metallogenic episode at around 170 Ma in the WQGP, which was coeval with the regional tectonic transition from a collisional compression to a late‐ to post‐collisional extension in the Qinling Orogen. Copyright © 2014 John Wiley & Sons, Ltd.